2020
DOI: 10.1093/annweh/wxaa031
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of Four Portable FTIR Instruments for Direct-on-Filter Measurement of Respirable Crystalline Silica

Abstract: Exposure to dusts containing respirable crystalline silica is a recognized hazard affecting various occupational groups such as miners. Inhalation of respirable crystalline silica can lead to silicosis, which is a potentially fatal lung disease. Currently, miners’ exposure to respirable crystalline silica is assessed by collecting filter samples that are sent for laboratory analysis. A more timely field-based silica monitoring method using direct-on-filter (DoF) analysis is being developed by researchers at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…NIOSH developed a direct-on-filter silica quantification method using portable FTIRs that can provide end-of-shift measurements on site [294,295]. However, interferences from other minerals can lead to inaccurate silica quantification [296,297]. Spectrum deconvolution and correction algorithms are still under development.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…NIOSH developed a direct-on-filter silica quantification method using portable FTIRs that can provide end-of-shift measurements on site [294,295]. However, interferences from other minerals can lead to inaccurate silica quantification [296,297]. Spectrum deconvolution and correction algorithms are still under development.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…At the focal point, the infrared beam in the four portable FTIR instruments evaluated by NIOSH is fixed and ranges from 6 to 9 mm [Ashley et al 2020], each of which is larger than the inlet openings commonly found in the traditional three-piece sampling cassette. The material of the cassette absorbs much of the IR beam, leaving insufficient signal for an accurate analysis.…”
Section: Niosh-developed Accessories For Ftir Instrumentationmentioning
confidence: 99%
“…This document contains guidance applicable to portable Fourier transform infrared spectroscopy (FTIR) instruments in general, though some instrument-specific guidance is also provided where necessary. While researchers from the National Institute for Occupational Safety and Health (NIOSH) have conducted extensive investigation on the use of four portable Fourier transform infrared spectroscopy (FTIR) instruments [Ashley et al 2020], other models of FTIR instruments may also be available and compatible with field-based monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that this method is not intended to be used for compliance determination. Four commercially available FTIR instruments (Figure 2.6) were used in initial NIOSH testing, with all units performing satisfactorily [Ashley et al 2020].…”
Section: Field-based Silica Analysismentioning
confidence: 99%